Safety and efficacy of newer anticonvulsant medications in pediatric epilepsy - Albert, Dara; Sieciechowicz, Diana; Kohrman, Michael (Journal of Pediatric Epilepsy, 2014)
We provide a comprehensive review of studies done since 2000 of the newest anticonvulsant medications in the treatment of pediatric epilepsy. Using the PubMed search engine we identified any studies referencing the use of the following eight anticonvulsants in children: brivaracetam, clobazam, ezogabine, felbamate, lacosamide, perampanel, vigabatrin and zonisamide. The papers reviewed included case reports, observational studies, retrospective and randomized-controlled trials between the year 2000 and 2014. Although there is abundant observational data on the safety and efficacy of these eight anticonvulsants in the treatment of pediatric epilepsy, there are only a limited number of randomized, placebo controlled trials of these drugs. Further study in this area is needed.
Keywords: Pediatric epilepsy; anticonvulsants